Tourism Geographic Information System using Google API Banten - DIDI KURNAEDI; Asep Surahmat; Erna Oktora; Manorang Sihotang (bit-Tech, 2019)
Banten Province as a Province adjacent to the Capital City of Jakarta and Banten Province is a province that is very well known because it has tourist areas in districts and sub-districts in Banten that have the main attraction to be visited by tourists, but the lack of information about existing tourist objects , and in searching for tourist information there are still many using maps manually, so we need an application that provides information services about tourist attractions in Banten, Web information system design provides information about the potential of the region as a tourist attraction in Banten Province. The geographic information system of web-based tourism in the province of Banten by using the Google Map API that can facilitate tourists searching, the location of users, interesting places and to find out the natural beauty and history in the province of Banten. This system is designed to make it easier for users to use and be more interactive. Supported by facilities to show the direction to the tourist attractions chosen by the user, as well as the addition of data visualization. This system is expected to be a guide and dissemination of travel information in Banten Province. Presentation of information in the form of images and maps will make it easier to understand users who will get the information effectively and efficiently. With the presence of this application is provided to meet the information needs of attractions in Banten Province